Regulatory Effects of Various IFN-β Formulations Therapy on CXC Chemokines CXCL1 and CXCL9 Gene/Protein Levels in Relapsing-Remitting Multiple Sclerosis Patients: Regulatory effects of various IFN-β formulations therapy on CXC chemokines - Pourmasumi, Soheila; Hassanshahi, Gholamhossein; Esmaeili-ranjbar, Faezeh; Jalali, Nazanin; Noroozi Karimabad, Mojgan (Iranian Journal of Pharmaceutical Sciences, 2024)
Multiple sclerosis (MS) is a complex clinical immune system disorder. The most common symptoms of MS are recurrent loss of myelin in conjunction with inflammation in the central nervous system (CNS). Chemokines, as important immune system components, play a role in immune responses. This project aimed to examine and compare the serum levels of CXCL1 and CXCL9 in patients with relapse-remitting MS (RRMS) following therapy with IFN-β formulations. Clinical specimens were collected from 50 unrelated healthy controls, as well as 40 RRMS patients treated with Cinnovex™ (CVX, Interferon beta-1a, made in Iran) and Avonex® (AVX, Interferon beta-1a, made in the USA). The fold changes in gene expression of CXCL1 and CXCL9 compared to the β-actin gene were determined using real-time PCR. The protein expression and serum levels of CXCL1 and CXCL9 were measured using the ELISA method. Data analysis was performed using the ANOVA test. The levels of CXCL1 and CXCL9 significantly increased, with greater upregulation observed with AVX and, to a lesser extent, with CVX. Our study results suggest that AVX is more effective than CVX in regulating the immune system, and the dosage of CVX may need to be increased to achieve a more pronounced therapeutic response in RRMS patients.